2021
DOI: 10.1007/s11356-021-16727-9
|View full text |Cite
|
Sign up to set email alerts
|

Viable medical waste chain network design by considering risk and robustness

Abstract: Medical waste management (MWM) is an important and necessary problem in the COVID-19 situation for treatment staff. When the number of infectious patients grows up, the amount of MWMs increases day by day. We present medical waste chain network design (MWCND) that contains health center (HC), waste segregation (WS), waste purchase contractor (WPC), and landfill. We propose to locate WS to decrease waste and recover them and send them to the WPC. Recovering medical waste like metal and plastic can help the envi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Many studies have so far reported how GSCM practices can lead to a decline in the environmental burden of production operations and residues as well as an increase in the competitiveness of the industry [2]. GSCM also seeks to remove or lessen negative environmental impacts (namely, air, water, and soil pollution) and waste resources (namely, energy, materials, and products) from the extraction or exploitation of raw materials to the nal consumption of products [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have so far reported how GSCM practices can lead to a decline in the environmental burden of production operations and residues as well as an increase in the competitiveness of the industry [2]. GSCM also seeks to remove or lessen negative environmental impacts (namely, air, water, and soil pollution) and waste resources (namely, energy, materials, and products) from the extraction or exploitation of raw materials to the nal consumption of products [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tirkolaee and Aydın [12] developed a sustainable MWM system for collection and transportation of MW in pandemics, they designed numerous various scales practical examples, solved the problem using CPLEX solver, and they compared diverse conditions. They also investigated the practical implications [13]. Moreover, He et al [14] optimized the problem of the automated MW sorting system by taking into account the operational flow of MW.…”
Section: Introductionmentioning
confidence: 99%
“…Their solution approach relies on the concept of value function and the later is characterized through a system of elliptic equations which is shown to have solutions. Among recent papers which contribute to the mathematical analysis of stochastic planning problem we mention [1], [3], [7], [21], [22] and [23].…”
mentioning
confidence: 99%
“…For the scalar case corresponding to the system (20)-( 21) an exact solution is obtained in the work of [3]. Unfortunately, for the system case we can't give a closed form solution but we provide an approximating sequence of functions which converges to the solution of ( 20)- (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation